2006
DOI: 10.1002/app.23135
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of cellulose acetate butyrate and poly(ethylene glycol) copolymer to blend with poly(3‐hydroxybutyrate)

Abstract: A two-step procedure was used to synthesize the cellulose acetate butyrate and poly(ethylene glycol) graft copolymer (CAB-g-PEG). By choosing the appropriate composition, the crosslinked graft copolymer or not could be obtained. Then, the CAB-g-PEG copolymer was blended with poly(3-hydroxybutyrate) (PHB), to further improve the mechanical properties of PHB. The results indicated that PHB and CAB-g-PEG that were not crosslinked were miscible over the entire composition range. As the CAB-g-PEG copolymer increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
(8 reference statements)
0
13
0
Order By: Relevance
“…Moreover, by varying parameters such as the degree of polymerization, polydispersities of the main chain and the side chains, gra density, and the distribution of the gras, a more polymeric material with more valuable properties may result. 217 Graing of cellulose acetate with other polymers such as poly(lactic acid), 232,233 poly(methyl methacrylate), 231,234 poly(hydroxybutyrate-co-valerate), 235 caprolactone, 32 polystyrene, 236 poly(ethylene glycol) and poly-(hydroxybutyrate) 237 with new and improved performance features including better conductivity, thermal stability, and other marked advantages with better control and property tuning capability has been reported in the literature.…”
Section: Cellulose Acetatementioning
confidence: 99%
“…Moreover, by varying parameters such as the degree of polymerization, polydispersities of the main chain and the side chains, gra density, and the distribution of the gras, a more polymeric material with more valuable properties may result. 217 Graing of cellulose acetate with other polymers such as poly(lactic acid), 232,233 poly(methyl methacrylate), 231,234 poly(hydroxybutyrate-co-valerate), 235 caprolactone, 32 polystyrene, 236 poly(ethylene glycol) and poly-(hydroxybutyrate) 237 with new and improved performance features including better conductivity, thermal stability, and other marked advantages with better control and property tuning capability has been reported in the literature.…”
Section: Cellulose Acetatementioning
confidence: 99%
“…The advantage of CMC is film formulation and the ability to blend with other polymers such as poly(ethylene glycol) (PEG), which is biocompatible, less toxic, and hydrophilic. 34 …”
Section: Introductionmentioning
confidence: 99%
“…PEG (Figure 1(b)) is an ideal candidate for blending with PHB, a flexible polymer with good solubility in both water and organic solvents; it is used in protein purification processes, as well as a drug carrier and various other pharmaceutical applications [10,11]. A range of PEGs can be synthesised with average molecular weights (Mn) from 106 (diethylene glycol, DEG) to 20,000.…”
Section: Introductionmentioning
confidence: 99%
“…Blending PHB with polyethylene glycol (PEG) reduces crystallinity and other physiochemical properties of the composite biomaterial [11,14]. Tan et al reported that PEG polymer chains remained mobile when PHB underwent crystallisation and moved to intra-and interspherulitic regions [15].…”
Section: Introductionmentioning
confidence: 99%